Kesiapan Manajemen Organisasi Pendidikan Dalam Menghadapi Dinamika Perubahan Kebijakan Negara - Habib Nur Muhammad; Sri Minarti (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study examines the readiness of educational organization management to cope with the dynamics of changes in national policy, particularly regarding the Free Nutritious Meals Program (MBG) as it relates to the national education budget. These policy changes pose challenges for schools that rely on School Operational Assistance (BOS), including SMP Al Mutamakkin Purwoasri Sukosewu as a free private school. The study aims to determine the readiness of school management in dealing with government policy changes that impact the management of the education budget. The study employs a qualitative approach using the case study method through interviews, observations, and documentation. The results indicate that the school implemented various adaptation strategies, such as budget efficiency, human resource optimization, strengthening school administration, and building partnerships with the community and educational foundations. However, limited funding sources remain a challenge in maintaining the quality of learning and school facilities. Therefore, the readinessof educational organization management is essential so that schools can survive and continue to provide optimal educational services amidst changes in government policy.